2016
DOI: 10.1073/pnas.1606160113
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-coil destabilizing residues in the group A Streptococcus M1 protein are required for functional interaction

Abstract: The sequences of M proteins, the major surface-associated virulence factors of the widespread bacterial pathogen group A Streptococcus, are antigenically variable but have in common a strong propensity to form coiled coils. Paradoxically, these sequences are also replete with coiled-coil destabilizing residues. These features are evident in the irregular coiled-coil structure and thermal instability of M proteins. We present an explanation for this paradox through studies of the B repeats of the medically impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…We proposed that these effects reflect a mesoscopic phase transition from soft and unordered to hard and ordered, presumably caused by a large-scale charge redistribution ( Song et al, 2011a , 2013 ). Local changes in molecular dynamics might be important in photoconversion and signaling by providing access to alternative topologies, as suggested by the capture-and-collapse model ( Stewart et al, 2016 ; see also below). On the other hand, the ‘ soft ’ state would allow for fast energy dissipation which is needed to keep a product in a local minimum, whereas the ‘ hard ’ state might provide for mechanochemistry and organized tension.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that these effects reflect a mesoscopic phase transition from soft and unordered to hard and ordered, presumably caused by a large-scale charge redistribution ( Song et al, 2011a , 2013 ). Local changes in molecular dynamics might be important in photoconversion and signaling by providing access to alternative topologies, as suggested by the capture-and-collapse model ( Stewart et al, 2016 ; see also below). On the other hand, the ‘ soft ’ state would allow for fast energy dissipation which is needed to keep a product in a local minimum, whereas the ‘ hard ’ state might provide for mechanochemistry and organized tension.…”
Section: Discussionmentioning
confidence: 99%
“…The M1 B-repeat region serves an essential function in GAS pathogenesis, as it is responsible for M1 binding to host fibrinogen (Fg) and formation of supramolecular M1-Fg complexes that induce neutrophil activation and transition to a proinflammatory state 14,41 . Based on these previous studies and taking into account our new findings, a potential scenario during GAS invasive infection is that released, soluble M1 protein first activates infiltrating neutrophils through the M1-Fg supramolecular complex, resulting in the recruitment and influx of macrophages to the site.…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples of proteins having non-heptad periodicities in the coiled-coil domain, but only a few studies have reported their functional significance 40,47,48 . In this work, we have explored the role of an extended helical region in E. coli co-chaperone GrpE, which forms a long non-ideal coiled-coil in the GrpE dimer.…”
Section: Altered Structural Stability Of Grpe Coiled-coil Affects Bacmentioning
confidence: 99%
“…Previously it has been reported that increased stability of a coiled-coil limits its conformational space, which alters its specific protein binding interfaces 47 . GrpE has a long extended structure which undergoes several conformational changes during thermal stress, and during its interaction with DnaK 16 .…”
Section: Altered Structural Stability Of Grpe Coiled-coil Affects Bacmentioning
confidence: 99%